1985
DOI: 10.1111/j.1745-4514.1985.tb00355.x
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Textural Defects in Cooked Reconstituted Legumes ?The Influence of Structure and Composition

Abstract: Legumes provide an important part of the world's protein requirements, as well as other nutrients, but they are underutilized as food. A major factor limiting expanded consumption is storage induced textural defects that prolong cooking time and demand correspondingly higher energy requirements for preparation. These defects, including the hard-to-cook phenomenon and hardshell, are initiated by structural and compositional factors but can be at least partially controlled by storage and processing conditions. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
6

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 79 publications
(55 reference statements)
3
103
0
6
Order By: Relevance
“…However, the phytic acid contents of all three legumes were higher than the levels reported for pigeon pea (2.2 mg/g) and bambara groundnut (2.9 mg/100 g) (Igbedioh, Olugbemi, & Akpapunam, 1994). Besides lowering the bioavailability of minerals and inhibiting the digestibility of proteins, phytic acid is also implicated in the ''hard-to-cook'' phenomenon of legumes (Stanley & Aguilera, 1985). However, its presence is also beneficial because it may have a positive nutritional role as an antioxidant and anticancer agent (Turner, Paphazy, Haygarth, & Mckelvie, 2002).…”
Section: Antinutritional Factorsmentioning
confidence: 66%
“…However, the phytic acid contents of all three legumes were higher than the levels reported for pigeon pea (2.2 mg/g) and bambara groundnut (2.9 mg/100 g) (Igbedioh, Olugbemi, & Akpapunam, 1994). Besides lowering the bioavailability of minerals and inhibiting the digestibility of proteins, phytic acid is also implicated in the ''hard-to-cook'' phenomenon of legumes (Stanley & Aguilera, 1985). However, its presence is also beneficial because it may have a positive nutritional role as an antioxidant and anticancer agent (Turner, Paphazy, Haygarth, & Mckelvie, 2002).…”
Section: Antinutritional Factorsmentioning
confidence: 66%
“…Softening of beans during cooking has been reported to be accompanied by structural changes in the seed (Rockland and Jones 1974;Sefa-Dedeh et al 1978). During cooking of legumes, the seeds undergo important physicochemical changes involving gelatinization and swelling of starch, denaturation of protein, solubilization of some of the polysaccharides, softening of the structure, and other physical and chemical changes, which result in a palatable texture (Stanley and Aguilera 1985). Cohesiveness (ratio of the positive force areas under the first and second compressions), gumminess and chewiness of the autoclaved mung bean were also found to be the lowest as compared to its soaked, germinated and cooked counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…bean lcommon) Michaels, T. E. et Stanley, D. W. 1991 Aguilera and Stanley (1985) reported that, based on combined data from four separate studies, beans stored for 10 mo at about 12% moisture and 25'C would require a 60% longer cooking time to soften. Antunes and Sgarbieri (1919) (Fig.…”
mentioning
confidence: 99%